The IMPLEMENTASI CORETAX ADMINISTRATION SYSTEM DENGAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT): ADMINISTRATION SYSTEM DENGAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Aksan; Esti Kiki Riski Sukran; mandala bakti (JAMB:Journal of Digital Business and Management, 2026)
This study aims to analyze the implementation of the Coretax Administration System in Indonesia through the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. This transformation is a strategic response to the challenges of the global digital economy, which demands data integration, service automation through pre-populated features, and risk-based oversight. The research method used is descriptive qualitative to explore taxpayer perceptions regarding four main pillars: performance expectations, effort expectations, social influence, and facilitating conditions. The results indicate that the primary benefit of Coretax lies in increased administrative efficiency and accuracy (performance expectancy). However, the complexity of the omnichannel system creates obstacles in the form of a steep learning curve (effort expectancy), especially for taxpayers with low digital literacy. Social validation from the professional community and tax consultants has proven crucial in reducing public resistance, while the stability of network infrastructure and responsiveness of technical assistance (facilitating conditions) determine the system's continued use. Real-world obstacles include the digital divide between regions, the risk of data migration, and the internal readiness of the tax authorities. The success of Coretax implementation depends not only on technological sophistication, but also on the harmony between system capabilities and user mental readiness. Tax authorities need to align performance expectations with inclusive ease of use. A well-targeted communication strategy and strengthened technical support are essential to shift taxpayer perceptions from mere mandatory compliance to trust-based technology adoption. Without this synergy, digitalization risks becoming a new administrative burden rather than an economic solution for the country.